EVALUASI PROGRAM PEMBERIAN TABLET TAMBAH DARAH (TTD) PADA REMAJA PUTRI DI WILAYAH KERJA PUSKESMAS SIMPANG IV SIPIN KOTA JAMBI - Dhevi Triana (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2026)
Anemia is a global public health problem that impacts health and economic development. To lower the incidence rate of anemia among female adolescents, the Indonesian government launched a program to provide iron supplements (IBF) in 2014. According to data from the Jambi City Health Office, in 2023, the Simpang IV Sipin Community Health Center (Puskesmas) had iron supplement coverage of 61.76%. In 2024, there was a significant decrease of 15.97% from the target. This figure indicates a serious challenge in achieving the target of 90% coverage by 2024, as stipulated in Minister of Health Regulation No. 13 of 2022. The purpose of this study was to evaluate the iron supplement program for adolescent girls in the Simpang IV Sipin Community Health Center's work area in Jambi City. A descriptive qualitative design was employed in conducting this research. Seventeen informants participated in the study. Information for this study was gathered using comprehensive, in-depth interviews, documentation, as well as observation. The analysis of the collected data was conducted using the NVivo qualitative data analysis program, in addition to triangulation of sources and techniques to ensure data validity. This study indicates that the human resources involved in this program are sufficient, but there were complaints about the lack of staff during field activities. Funds are sufficient to implement the program, relying on BOK funds for transportation costs and the availability of facilities and infrastructure that do not comply with program guidelines. In light of the findings, it is advisable for the Community Health Centers utilize educational media through social media that can be displayed on school equipment, conduct outreach to both health center teachers and adolescent girls, and improve facilities and infrastructure.